2016
DOI: 10.14238/pi43.1.2003.14-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and prognostic factors of intracranial hemorrhage in children

Abstract: Objective Finding the characteristics and risk factors associatedwith prognosis in children suffering from intracranial hemorrhage.Methods This was a retrospective medical record review of chil-dren (older than 1 month old) admitted with intracranial hemor-rhage to the Department of Child Health the Sanglah Hospital,Denpasar, during the period of January 1998 to December 2000.Prognostic factors were identified by chi-square and multivariateanalysis with significance of p<0.05Results There were 56 patients e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(12 reference statements)
0
1
0
2
Order By: Relevance
“…[5][6][7]10 Perbedaan tersebut mungkin dikarenakan usia subyek pada penelitian ini lebih muda. Pada anak yang lebih muda, kecenderungan perdarahan subdural terjadi akibat tulang tengkorak yang masih elastis sehingga adanya akselerasi dan deselerasi pada regio oksipital dan fisura interhemisfer posterior menyebabkan perdarahan karena di regio tersebut sutura lambdoidea dan sutura sagitalis bertumpang tindih, akibatnya pergerakan tulang dapat menyebabkan robekan dari sinus duramater.…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…[5][6][7]10 Perbedaan tersebut mungkin dikarenakan usia subyek pada penelitian ini lebih muda. Pada anak yang lebih muda, kecenderungan perdarahan subdural terjadi akibat tulang tengkorak yang masih elastis sehingga adanya akselerasi dan deselerasi pada regio oksipital dan fisura interhemisfer posterior menyebabkan perdarahan karena di regio tersebut sutura lambdoidea dan sutura sagitalis bertumpang tindih, akibatnya pergerakan tulang dapat menyebabkan robekan dari sinus duramater.…”
Section: Pembahasanunclassified
“…Penelitian sebelumnya melaporkan bahwa adanya gangguan perdarahan akan sangat memengaruhi mortalitas, dengan angka kematian subyek dengan gangguan perdarahan hingga 41%. 10,12,13 Pemanjangan apTT menunjukkan derajat gangguan perdarahan dan kadar Hb dapat berhubungan dengan derajat dan lama perdarahan yang terjadi. Penurunan GCS dan refleks cahaya mungkin mencerminkan derajat proses desak ruang akibat peningkatan tekanan intrakranial.…”
Section: Pembahasanunclassified
“…2 A study conducted by Kardana et al found that from 56 children with intracranial hemorrhages, 43 children (77%) were aged less than 1 year and 40 children (71%) had SIH without any history of trauma. 3 An initial study conducted from January 2007 to December 2011 at Mohammad Hoesin Hospital in Palembang found 55 cases of intracranial hemorrhage, of whom 52 (94%) children were less than 1 year old, with an average age of 2.6 months. Fifty of these children (90%) had no apparent history of head trauma.…”
mentioning
confidence: 99%